Drought Tolerance Screening and Estimation of Genetic Variation among Some Wheat Cultivars Using Physiological and SRAP markers - Saeed, Badr Eldin A.E.; El Siddig, Marmar A.; Osman, Aisha O.; El Hussein, Adil A. (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
The present study was carried out to screen 12 Sudanese wheat (Triticum aestivum L.) cultivars for their in vivo response to drought stress and to identify diverse sources that could accelerate the development of improved wheat varieties better adapted to dry climate in Sudan. Genetic diversity was studied by sequence-related amplified polymorphism (SRAP) markers. Results of the in vivo screening showed significant varietal differences (p<0.05) in most of the traits examined indicating the possibility of selection for drought tolerant among the cultivars. Under stress conditions significant (p<0.05) reductions in plant height and number of leaves were observed as compared to the control. Significant reduction in stem diameter, head length and head excursion length was only observed when the plants were watered at 7-days intervals. The most susceptible cultivars, that scored the highest Integrated Susceptibility Index (ISI) values, were Imam, Argeen and Sasareeb. Genetic polymorphism indicated that only 24 out of the 64 (37.5 %) markers tested produced different-sized fragments with DNA of one or more of the tested cultivars. The number of fragments detected for each cultivar ranged from 44 for cultivar Imam to 57 for Nebta. The lowest genetic similarity of 55% was detected between cultivars Imam and Tagana, while the highest similarity (86%) was detected between cultivars Condor and Naser. The data generated from morphological, physiological and molecular markers were combined and utilized to construct a similarity matrix based on Jaccard’s coefficient. Values indicated that the closest cultivars were Debiera and Condor, while the most distant ones were Tagana and Imam. Principal coordinate analysis (PCoA) showed a scattered pattern for the 12 cultivars with cultivar Imam, which showed the highest morphological mean performance and the highest ISI values, standing far away from all other cultivars. Results of this study will help in the selection of germplasms in wheat improvement breeding programs.